Assessing combinatorial effects of HIV infection and former cocaine dependence on cognitive control processes: A high-density electrical mapping study of response inhibition. (1st September 2021) - Wakim, Kathryn-Mary; Freedman, Edward G.; Molloy, Ciara J.; Vieyto, Nicole; Cao, Zhewei; Foxe, John J.
Abstract: Stimulant drug use in HIV + patients is associated with poor personal and public health outcomes, including high-risk sexual behavior and faster progression from HIV to AIDS. Inhibitory control--the ability to withhold a thought, feeling, or action--is a central construct involved in the minimization of risk-taking behaviors. Recent neuroimaging and behavioral evidence indicate normalization of inhibitory control processes in former cocaine users as a function of the duration of drug abstinence, but it is unknown whether this recovery trajectory persists in former users with comorbid HIV. Here, we investigate the neural correlates of inhibitory control in 103 human subjects using high-density EEG recording as participants performed a Go/NoGo response inhibition task. Four groups of participants were recruited, varying on HIV and cocaine-dependence status. Electrophysiological responses to successful inhibitions and behavioral task performance were compared among groups. Results indicate persistent behavioral and neurophysiological impairment in HIV+ patients' response inhibition despite current abstinence from cocaine. Analysis of task performance showed that HIV+ abstinent cocaine-dependent participants demonstrate the lowest performance of all groups across all metrics of task accuracy. Planned comparisons of electrophysiological components revealed a main effect of scalp site and an interaction between HIV-status and scalp site on N2 amplitudes during successful inhibitions. Analysis of the P3 time region showed a main effect of scalp site and an interaction between HIV-status and cocaine dependence. These results suggest synergistic alterations in the neurophysiology of response inhibition and indicate that abstinence-related recovery of inhibitory control may be attenuated in patients with HIV. Highlights: Cocaine dependence (CD) is a common comorbidity of HIV infection. Combined effects of CD and HIV on neural function were assessed with task-based EEG. Additive effects of HIV and CD were observed on task performance. Interactive effects on EEG amplitude were observed over fronto-central scalp regions.